Harakatlar strategiyasi asosida ta’lim va fan sohasidagi qonunchilik hamda ilk islohotlar - Kudaybergenova, T (SCIENCE and SOCIETY, 2017)
The article deals with legislation and first concepts in the field of educations and science based on the strategy of actions.
Keywords: strategic аction; teaching; science; academy; preschool establishment; curriculum